Rancang Bangun Sistem Monitoring Asap Berbahaya dan Pengunaan Hepa Filter Guna Efisiensi Daya Terhadap Sistem Pembuangan - Waleleng, Kevin Moses; Saputra, I Putu Gede Hendra (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 2 (2024): JNATIA Vol. 2, No. 2, Februari 2024DO - 10.24843/JNATIA.2024.v02.i02.p13, 2024)
Wireless Sensor Networks are a combination of Monitoring, Controlling and Data Receiving Systems. Wireless sensor networks are used in various fields, environmental activity monitoring, home monitoring, agricultural monitoring, and many other things. In terms of monitoring an environment, the levels of conditions that can cause dangerous things include smoke, fire and toxic gases. Because of this, an early detection system is very necessary. This system can be combined to be able to provide early notification signals and then take preventive steps to anticipate things that have the potential to result in risks or fatal events. In this design, the devices used will be an Arduino Uno microcontroller module, MQ-2 sensor, LED, buzzer, fan and relay. The method used is an experimental research method that can correctly test hypotheses regarding casual relationships through a design science research method (DSRM) stage pattern. Then testing is carried out by placing the system in a predetermined environment and then the data collection process is carried out periodically for certain conditions.